ESRA19-0034 Bilateral subpectoral nerve catheters in the management of acute sternal fracture. (30th August 2019) - Hooper, J; Sussman, M; Kausik, D; Gorecha, M
Abstract : Background and aims: A case report of the use bilateral subpectoral nerve catheters in a 57-year-old patient with severe acute pain secondary to a traumatic sternal fracture. the pain was opioid-resistant and unchanged by systemic analgesia. It was preventing the patient from mobilizing, deep breathing and coughing. Methods: Consent was obtained. He was positioned supine. Aseptic technique was adhered to. a SonoSite® ultrasound high frequency linear probe was placed 2cm lateral to the sternum in the parasagittal plane and a Pajunk E-Cath nerve catheter needle was inserted in plane from caudal to cephalad in the fascial plane between pectoralis major and external intercostal muscle. 10 ml of 0.25% levobupivacaine was injected bilaterally, and the catheters were subsequently topped up every 12 hours. Results: Within 5 minutes of a single dose of local anaesthetic the patient was pain free, able to deep breath, cough and mobilise. He was discharged home after 3 days of treatment. Conclusions: In patients with isolated sternal fractures, severe pain is the most frequently reported complaint and this can lead to further complications, such as hospital-acquired pneumonia. Furthermore, high dose opioid therapy can lead to multiple adverse events and is often ineffective in chest wall fractures. This case highlights that subpectoral nerve catheters used in the management of sternal fractures can reduce pain. Further research if required to determine its role in reducing opioid-associated complications, incidence of pneumonia and inpatient length of stay.